PENGARUH PENERAPAN MODEL CONTEXTUAL TEACHING AND LEARNING BERBANTUAN MEDIA ASSEMBLR EDU TERHADAP KEMAMPUAN LITERASI SAINS SISWA SEKOLAH DASAR - Azzahra Salsabila Aldila; Puji Rahayu; Nenden Permas Hikmatunisa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to find out the effect and improvement of the application of the Contextual Teaching and Learning learning model assisted by Assemblr Edu media on the science literacy skills of elementary school students. Science literacy is an important skill in learning Science and Social Science (IPAS) because it helps students understand scientific concepts and relate them to everyday life. However, various studies show that students' science literacy skills in Indonesia are still relatively low. This study used a quasi-experimental method with a non-equivalent control group design. The research sample was fourth grade students of SDN Teluk Pucung 1 Bekasi which was divided into two groups, namely the experimental class and the control class. The instrument used was a description test to measure science literacy skills. The results of data analysis show that learning with the Contextual Teaching and Learning learning model assisted by Assemblr Edu media has increased by 0.77 which is in the high category. Then there is an effect of the Contextual Teaching and Learning model assisted by Assemblr Edu of 54.2%. In this study, it can be concluded that the Contextual Teaching and Learning model assisted by Assemblr Edu media effectively influences and improves students' science literacy skills in IPAS learning.